„Codzienność – niecodziennie” - postawy studentów pedagogiki przedszkolnej i wczesnoszkolnej wobec innowacyjnej strategii nauczania - Kosek, Agnieszka (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
The paper presents the attitude of future pedagogues towards an unusual way of teaching which is proposed by the Storyline Method. In a group of pedagogy studies students research was conducted which aim was to examine the described problem. In the first part of the article the focus was put on the description of institutional and non-institutional forms of teachers education. In the further part the characteristic of self-studies was shown and the results of the studies were analyzed.
Keywords: codzienność; formy kształcenia; kształcenie akademickie; kształcenie nauczycieli; metoda storyline; postawy studentów